2017
DOI: 10.1007/s10086-017-1652-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in intrinsic wood properties of Melia azedarach L. planted in northern Vietnam

Abstract: Variations in intrinsic wood properties [growth ring width (GRW), specific gravity (SG), fiber length (FL), and microfibril angle (MFA)] of 17-19-year-old Melia azedarach trees grown in two sites in northern Vietnam were investigated for effective utilization of the wood. Five discs were collected at 0.3-, 1.3-, 3.3-, 5.3-, and 7.3-m heights above the ground. The estimated mean GRW, SG, FL, and MFA were 7.44 mm, 0.548, 1.07 mm, and 14.65°, respectively. There were significant (P \ 0.05) differences among trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
3
13
1
Order By: Relevance
“…Therefore, transverse shrinkage increases and longitudinal shrinkage decreases with the decrease of MFA. In the previous study [15], we found that MFA of M. azedarach followed a declining trend from near the pith (16°) to bark (12°) (measured at only 1.3 m heigh above the ground) which was the opposite trend of transverse shrinkages (α T and α R ) observed in this study. Hence, the within-tree variation in MFA together with density could explain to be larger of transverse shrinkage in the outer wood than in the inner wood presented in this study.…”
Section: Bd and Transverse Shrinkagecontrasting
confidence: 75%
See 1 more Smart Citation
“…Therefore, transverse shrinkage increases and longitudinal shrinkage decreases with the decrease of MFA. In the previous study [15], we found that MFA of M. azedarach followed a declining trend from near the pith (16°) to bark (12°) (measured at only 1.3 m heigh above the ground) which was the opposite trend of transverse shrinkages (α T and α R ) observed in this study. Hence, the within-tree variation in MFA together with density could explain to be larger of transverse shrinkage in the outer wood than in the inner wood presented in this study.…”
Section: Bd and Transverse Shrinkagecontrasting
confidence: 75%
“…The north and south sides of each tree were marked before felling. Sample trees were the same as those used in the previous study on variation in intrinsic wood properties (Table 2) [15].…”
Section: Samplingmentioning
confidence: 99%
“…A better understanding of the wood variability within tree is of value to both wood quality improvement and efficient wood processing and utilization. In a previous study [5], we reported that the Melia azedarach trees planted in site 2 (Son La provenance) were higher in wood specific gravity and fiber length and smaller in microfibril angle of the S 2 layer of cell wall than those planted in site 1 (Tuyen Quang provenance). This implies that mechanical properties on wood of Melia azedarach planted in site 2 may also be higher than those planted in site 1.…”
Section: Introductionmentioning
confidence: 77%
“…At a reaction time longer than 630 minutes, a small peak assigned to s 2p3/2 of aluminum sulphate (Al 2 [SO 4 ] 3 )) including Al-O-S = O bonds in its crystal structure was observed at a binding energy of 169 eV in the XPS spectrum of SG-M catalyst. [10,43] The S/Al ratio of SG-M catalyst was determined to be 0.011 at the end of the stability test (after 630 minutes of reaction time). Although 100% sulphur selectivity was obtained with SG-M, the H 2 S conversion decreased to 59% after 630 minutes of reaction time.…”
Section: Catalytic Activity Tests Of Fresh Catalystsmentioning
confidence: 99%